HUBUNGAN KOMUNIKATOR DALAM ELECTRONIC WORD OF MOUTH DENGAN KEPUTUSAN PEMBELIAN FOLLOWERS AKUN INSTAGRAM KULINERPKU - Wulandari, Fitri; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Electronic word of mouth is positive or negative statement about a product or a company made by potential customers, current customers or former customers over the internet. E-WOM now becomes an effective marketing communications media because it low cost and the great effort and instagram became one of the media that used in marketing products/services. In the context of information online, consumers tend to trust that information with a high degree of source credibility is compared to a low source credibility to influence consumer behavior. This research starts from Elaboration Likelihood models. In this research, in making purchase decisions at the restaurant/CafÃ© which is informed by Kulinerpkuâs admin as communicators of EWOM, an individual has the possibility to process them in the Central and peripheral route that is related to the sides of the Communicator and his message. The purpose of this research was to know relationship communicators in electronic word of mouth with purchase decision followers of instagram account Kulinerpku. The methods used in this research is quantitative method of explanation. Data collection techiques in this study using questionnaire. The number of samples for this studi were 166 respondents. Sampling using Judgemental Sampling. To find out how much relationship between both side variables, the researchers used the analysis of correlation pearson product moment. Questionnaire for data processing, carried out using the statistical program Product And Service Solution (SPSS) version of Windows 23. The results of the research on the relationship between communicators in electronic word of mouth with purchase decisions followers of instagram account Kulinerpku Obtained t value of 0,675 with probability level 0,005. This means that the value is included in the category of strong interpretation guidelines in accordance with the correlation coefficient. It shows that there is a correlation of communicators in Electronic word of mouth with purchase decisions followers Kulinerpku instagram account H0 is rejected and Ha is received.